Synthesis of 1,4-azaphosphinine nucleosides and evaluation as inhibitors of human cytidine deaminase and APOBEC3A - Kvach, Maksim V.; Harjes, Stefan; Kurup, Harikrishnan M.; Jameson, Geoffrey B.; Harjes, Elena; Filichev, Vyacheslav V. (Beilstein Journal of Organic Chemistry, 2024)
Nucleoside and polynucleotide cytidine deaminases (CDAs), such as CDA and APOBEC3, share a similar mechanism of cytosine to uracil conversion. In 1984, phosphapyrimidine riboside was characterised as the most potent inhibitor of human CDA, but the quick degradation in water limited the applicability as a potential therapeutic. To improve stability in water, we synthesised derivatives of phosphapyrimidine nucleoside having a CH2 group instead of the N3 atom in the nucleobase. A charge-neutral phosphinamide and a negatively charged phosphinic acid derivative had excellent stability in water at pH 7.4, but only the charge-neutral compound inhibited human CDA, similar to previously described 2'-deoxyzebularine (Ki = 8.0 ± 1.9 and 10.7 ± 0.5 µM, respectively). However, under basic conditions, the charge-neutral phosphinamide was unstable, which prevented the incorporation into DNA using conventional DNA chemistry. In contrast, the negatively charged phosphinic acid derivative was incorporated into DNA instead of the target 2'-deoxycytidine using an automated DNA synthesiser, but no inhibition of APOBEC3A was observed for modified DNAs. Although this shows that the negative charge is poorly accommodated in the active site of CDA and APOBEC3, the synthetic route reported here provides opportunities for the synthesis of other derivatives of phosphapyrimidine riboside for potential development of more potent CDA and APOBEC3 inhibitors.
Keywords: APOBEC3; cytidine deaminase; enzyme activity; inhibitor; nucleoside; nucleotide; zebularine